Aspirin is associated with a reduction in mortality rate for patients with sepsis-induced coagulopathy: a retrospective cohort study - Xu, Dan; Li, Jingyuan; Wang, Zhiyuan; Li, Junda; Zhao, Qingyu; Zhao, Qiannan; Xie, Fei; Li, Tingting; Chen, Jiying; Wang, Xiya; Zhou, Xin; Guo, Yuan; et al. (Frontiers in Pharmacology, 2025)
BackgroundThis study aimed to examine whether aspirin reduces mortality in patients with sepsis-induced coagulopathy (SIC).MethodsIn this retrospective cohort study, 1,194 patients with SIC were identified from the Medical Information Mart for Intensive Care (MIMIC)-IV database. The primary outcome was 28-day all-cause mortality. Secondary outcomes included 90-day and 1-year all-cause mortality, as well as length of stay in the intensive care unit (ICU). Missing data were handled using multiple imputation, and baseline differences between groups were adjusted through propensity score matching (PSM). The association between aspirin therapy and mortality in SIC patients was evaluated using both univariate and multivariate Cox proportional hazards models. Additionally, subgroup analyses were performed to investigate the effect of aspirin across different populations and to assess the impact of aspirin dosage on clinical outcomes. External validation was subsequently conducted to confirm the robustness of the findings.ResultsAfter PSM, 280 aspirin-treated patients were matched with 280 non-aspirin patients. Aspirin use was associated with significantly lower 28-day mortality (11.8% vs. 29.3%, p < 0.001), 90-day mortality (16.8% vs. 33.6%, p < 0.001), and 1-year mortality (22.1% vs. 42.1%, p < 0.001), as well as a shorter median ICU stay (2.19 vs. 3.14 days, p < 0.001) among patients with SIC. Multivariate Cox regression further confirmed the protective effect of aspirin on 28-day (hazard ratio [HR]: 0.45, 95% confidence interval [CI]: 0.29–0.7), 90-day (HR: 0.55, 95% CI: 0.37–0.81), and 1-year mortality (HR: 0.59, 95% CI: 0.42–0.83). Additionally, when comparing the efficacy of low-versus high-dose aspirin therapy, the low-dose group demonstrated significantly lower 28-day, 90-day, and 1-year mortality rates. External validation further supported these findings, showing reduced 28-day mortality (15.3% vs. 35.9%, p = 0.01) and improved overall survival (p = 0.0037) in the aspirin-treated group.ConclusionAspirin use was associated with reduced 28-day, 90-day, and 1-year mortality, as well as a shorter ICU stay in patients with SIC. These findings were confirmed through external validation.